2022
DOI: 10.1093/bib/bbab610
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the etiology and role in oncogenic transformation of the CpG island methylator phenotype: a pan-cancer analysis

Abstract: Numerous cancer types have shown to present hypermethylation of CpG islands, also known as a CpG island methylator phenotype (CIMP), often associated with survival variation. Despite extensive research on CIMP, the etiology of this variability remains elusive, possibly due to lack of consistency in defining CIMP. In this work, we utilize a pan-cancer approach to further explore CIMP, focusing on 26 cancer types profiled in the Cancer Genome Atlas (TCGA). We defined CIMP systematically and agnostically, discard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 103 publications
(153 reference statements)
0
14
0
Order By: Relevance
“…Our study demonstrated the utility of the cfMeDIP-seq assay in studying the methylome of SCLC and demonstrated that plasma methylation is representative of tissue (Figure 1C) and is enriched in regions that are cancer specific (Figure 1D, Figure 1E) 13 . To our knowledge, this is the largest study to comprehensively examine the DNA methylation of SCLC patients by whole genome analysis.…”
Section: Discussionmentioning
confidence: 60%
“…Our study demonstrated the utility of the cfMeDIP-seq assay in studying the methylome of SCLC and demonstrated that plasma methylation is representative of tissue (Figure 1C) and is enriched in regions that are cancer specific (Figure 1D, Figure 1E) 13 . To our knowledge, this is the largest study to comprehensively examine the DNA methylation of SCLC patients by whole genome analysis.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, studies on the CpG Island methylator phenotype (CIMP+) have highlighted the association of SETD2 and DNA methylation in cancer, with gene body hypomethylation and promoter hypermethylation which is in line with our results [ 45 – 47 ]. While SETD2 mutations can drive CIMP + phenotypes, not all CIMP + phenotypes occur due to SETD2 mutations and Yates et al found that SETD2 was a driver of CIMP + in only 3 cancer types [ 46 ]. Further, several mutations may drive CIMP + in the same cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the utility of the cfMeDIP-seq assay in studying the methylome of SCLC and demonstrated that plasma methylation is representative of tissue ( Figure 1 C) and is enriched in regions that are cancer specific ( Figures 1 D and 1E). 23 We report one of the largest studies to comprehensively examine the DNA methylation of patients with SCLC by whole-genome analysis alongside a contemporaneously published study that demonstrates the value of liquid biopsy assays. 21 In contrast to prior tissue-based studies, 8 , 9 our genome-wide approach profiled methylated DNA loci beyond 450K/EPIC array probes and identified hypermethylated noncoding and repeat elements (e.g.…”
Section: Discussionmentioning
confidence: 99%